ANALISIS PENCATATAN DAN PELAPORAN BELANJA LANGSUNG PADA BADAN PELAKASANA PENYULUHAN DAN KETAHANAN PANGAN KOTA MANADO - Walangitan, Cheny; Morasa, Jenny; Kalalo, Meily (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Work Units (SKPD) is part of the local governments that perform the task of government and public services, either directly or indirectly. To carry out their tasks and functions, the local work unit is allocated funds (budget). Therefore iu, also called the head SKPD budget (PA). Research Object is the Implementing Agency and the Food Security Extension Manado City is a regional work units (SKPD) is located in the district Mapanget. The purpose of this study was to analyze the recording and reporting of direct expenditure. The method used in this research is descriptive method that aims to understand and describe the data obtained in the form of records and expense reports. Research results in the recording of the Implementing Agency and the Food Security Extension Manado City in accordance with Government Regulation No. 71 of 2010. The monthly report treasurer in the format and description are in accordance with Government Regulation No. 71 of 2010 on government accounting standards. Keywords: Recording, Reporting, Direct Spending